0006 The Role of Stress in Sleep in Night Shift Workers: Going Beyond Circadian Misalignment. (27th May 2020) - Schaap, E; Sagong, C; Cuamatzi Castelan, A S; Sayed, J; Roth, T; Drake, C L; Cheng, P
Abstract: Introduction: Despite a growing need for nighttime work, few studies have characterized the causes of sleep disturbance in night shift workers beyond circadian misalignment. Recent research suggest that high sleep reactivity to stress (a predisposition for sleep disturbance due to stress) may also lead to sleep difficulties in shift workers. This study investigated if sleep reactivity is an independent predictor of daytime sleep disturbances after controlling for circadian phase. Methods: Night shift workers (N= 48) completed an 8 hour polysomnography (PSG) during the daytime following a night shift (9am - 4pm). Circadian phase was measured using melatonin assays of saliva samples collected over 24 hours under dim light (<10 lux; Dim Light Melatonin Onset [DLMO]). Sleep reactivity was measured using the Ford Insomnia Response to Stress Test (FIRST). Linear regressions were conducted with PSG sleep parameters as outcome variables: difficulty falling asleep (Sleep Onset Latency [SOL] and Latency to Persistent Sleep [LPS]), difficulty staying asleep (Wake After Sleep Onset [WASO]), and sleep duration (Total Sleep Time [TST]). FIRST was tested as a predictor controlling for DLMO. Results: After controlling for circadian phase, higher FIRST scores was associated with more difficulty staying asleep (WASO: t [45]=4.059, p <0.001) and shorter sleep duration (TST: t[45] = -4.403, p<0.0001), but not predictive of difficulty falling asleep (SOL: p> 0.05). However, higher FIRST scores did predict a longer latency to persistent sleep (LPS: t [45]=2.272, p <0.05). Conclusion: These results suggest that sleep reactivity to stress and circadian misalignment are independent processes that are both associated with disrupted daytime sleep in night shift workers. Given that night shift work can also cause psychosocial stress, treatments focused on circadian misalignment alone may not be sufficient. Our study highlights the need to consider sleep reactivity in the clinical management of shift work disorder. Support: Support for this study was provided to PC by NHLBI (K23HL138166).